Pemeriksaan Kesehatan dan Pembentukan Kader Lansia Melati di Nagari Sungai Buluh Selatan, Padang Pariaman - Fitri Mailani; Rahmi Muthia; Emil Huriani; Elvi Oktarina; Vebby Fitri Nur’arita (Warta Pengabdian Andalas, 2023)
The causes of diseases in the elderly come from within the body (endogenous), as this occurs due to a decline in the function of various organs inside the body, resulting in reduced production of hormones, enzymes, and substances needed for the immune system. Providing related activities in the form of health checks for older people and the formation of elderly cadres is expected to impact improving the health of older people. This activity aims to provide community service by conducting health checks and forming Melati elderly cadres in the Sungai Buluh Selatan Village. The method of this activity is to perform health checks, including blood pressure, blood sugar levels, cholesterol, and uric acid checks, followed by providing education related to the examination results and the formation of Melati elderly cadres. The results of this activity showed that 22 (33.3%) of the elderly had prehypertension in systolic blood pressure, 19 (28.8%) of the elderly had hypertension in diastolic blood pressure, 11 (16.7%) of the elderly had blood sugar levels >200 mg/dL, 22 (33.3%) of the elderly had uric acid levels >7 mg/dL, and 40 (60.6%) of the elderly had cholesterol levels >200 mg/dL. To organize social activities and as peer educators for the elderly, five older adults were selected as cadres in the MELATI elderly community. Health examination activities for older people will continue as a routine activity and improve the quality of training for cadres.